Agency and Signaling Perspectives on Working Capital Turnover, Debt to Equity Ratio, and Profitability in PT Gudang Garam Tbk (2013–2023) - Zelpani, Den Ayu; Budi, Saksono (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study investigates the influence of Working Capital Turnover (WCTO) and Debt to Equity Ratio (DER) on the Net Profit Margin (NPM) of PT Gudang Garam Tbk during the 2013–2023 period. Using a quantitative approach with secondary financial data, hypothesis testing was conducted through the partial (t-test) and simultaneous (F-test) significance tests at a 5% alpha level. Data analysis employed SPSS version 24. The results indicate that WCTO has a significant partial effect on NPM, as reflected by a t-value of –2.819 < 2.306 and a significance level of 0.0223 < 0.05. Conversely, DER shows no significant partial effect on NPM, with a t-value of 1.666 < 2.306 and a significance value of 0.134 > 0.05. Simultaneously, WCTO and DER have a significant combined effect on NPM, evidenced by an F-value of 4.921 > 4.26 and a significance level of 0.040 < 0.05. The Adjusted R-squared of 43% indicates that the model explains nearly half of the variation in profitability.